PENGEMBANGAN SIMULASI DISKRIT PADA PERANCANGAN ULANG TATA LETAK PRODUKSI UD. GAJAH DELTA GUNA MEMINIMASI ONGKOS MATERIAL HANDLING - Rico Alexsander Yulius Malonda; Putu Eka Dewi Karunia Wati (LPPM Universitas Bina Bangsa, 2023)
Layout is the most important aspect in an industry. A good production layout will increase efficiency in the production process. UD.Gajah Delta is a business unit engaged in the production of cooking equipment. The layout at UD. Gajah Delta is still in a condition that has not considered the smooth movement of materials. The purpose of this research is to redesign the layout of the production process which produces a proposed layout with low material movement costs. Redesign starts from data collection. The data that has been collected is then processed using the From To Chart calculation method to minimize material movement. The proposed layout chosen was the 25th Trial From To Chart with a total Forward and Backward value of 20,592.4. The proposed layouts are as many as 2, with the advantages and disadvantages of each. The proposed layout design is then simulated using the Flexsim software for accuracy in implementing the layout redesign